2015
DOI: 10.5194/angeo-33-637-2015
|View full text |Cite
|
Sign up to set email alerts
|

GPS phase scintillation at high latitudes during geomagnetic storms of 7–17 March 2012 – Part 1: The North American sector

Abstract: Abstract. The interval of geomagnetic storms of 7-17 March 2012 was selected at the Climate and Weather of the Sun-Earth System (CAWSES) II Workshop for group study of space weather effects during the ascending phase of solar cycle 24 (Tsurutani et al., 2014). The high-latitude ionospheric response to a series of storms is studied using arrays of GPS receivers, HF radars, ionosondes, riometers, magnetometers, and auroral imagers focusing on GPS phase scintillation. Four geomagnetic storms showed varied respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…As already stated for ICME days, this is a result of more frequent expansion of the auroral oval during intense auroral events that can include SAPS events and increased activity in the polar cap including the tongue of ionization (TOI) that is drawn from dense SED plasma producing patches of enhanced plasma density. In case studies, weak-to-moderate scintillation was found at sub-auroral latitudes, collocated with SAPS, and events of moderate-to-strong scintillation associated with TOI and polar patches were observed in the polar cap (Prikryl et al, 2013b(Prikryl et al, , 2015a.…”
Section: Scintillation Occurrence Dependence On Geomagnetic Activitymentioning
confidence: 95%
See 2 more Smart Citations
“…As already stated for ICME days, this is a result of more frequent expansion of the auroral oval during intense auroral events that can include SAPS events and increased activity in the polar cap including the tongue of ionization (TOI) that is drawn from dense SED plasma producing patches of enhanced plasma density. In case studies, weak-to-moderate scintillation was found at sub-auroral latitudes, collocated with SAPS, and events of moderate-to-strong scintillation associated with TOI and polar patches were observed in the polar cap (Prikryl et al, 2013b(Prikryl et al, , 2015a.…”
Section: Scintillation Occurrence Dependence On Geomagnetic Activitymentioning
confidence: 95%
“…This can be attributed to most intense events when auroral oval expanded further equatorward and SAPS/SED events occurred (Prikryl et al, 2013b(Prikryl et al, , 2015c, which is more often the case during ICME disturbances. On the other hand, CIR/HSSs are known to be permeated with high-amplitude solar wind Alfvén waves coupling to the dayside magnetopause and producing copious patches (Prikryl et al, 1999(Prikryl et al, , 2015a. Polar patches are the main cause of scintillation in the polar cap but also in the nightside auroral oval as they evolve into auroral blobs (Jin et al, 2014).…”
Section: Scintillation Occurrence Dependence On Geomagnetic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…At high and middle latitudes, GPS phase scintillation observations have shown that ionospheric irregularities are primarily enhanced in the cusp in association with storm-enhanced plasma density (SED). A tongue of ionization (TOI) can be formed and broken into patches that are transported into the polar cap (e.g., Aarons et al, 2000;De Franceschi et al, 2008;Spogli et al, 2009Spogli et al, , 2013aPrikryl et al, 2011Prikryl et al, , 2015aPrikryl et al, , b, 2016Thomas et al, 2013;Horvarth and Lovell, 2015). In the auroral oval, GPS scintillation has been observed during energetic particle precipitation events (Skone et al, 2008;Kinrade et al, 2013;Prikryl et al, 2013aPrikryl et al, , b, 2016.…”
mentioning
confidence: 99%
“…Most of the work done on specific geomagnetic storms refers to effects in the ionosphere at different sectors in the Northern Hemisphere (e.g., Yizengaw et al, 2005;De Franceschi et al, 2008;Spogli et al, 2009;Prikryl et al, 2011Prikryl et al, , 2015aPrikryl et al, , b, 2016Danilov, 2013;Thomas et al, 2013;Hovart and Lovell, 2015;and references therein) where there is a dense network of instrumentation for ionospheric studies. In contrast, in the Southern Hemisphere where the network of instrumentation is sparse, there is less work and most ionospheric studies have been done in the Australian and African sectors.…”
mentioning
confidence: 99%